The nuclear receptor PPARγ controls progressive macrophage polarization as a ligand-insensitive epigenomic ratchet of transcriptional memory - Daniel, B; Nagy, G; Czimmerer, Z; Horvath, A; Hammers, D; Cuaranta-Monroy, I; Poliska, S; Tzerpos, P; Kolostyak, Z; Hays, T; Patsalos, A; Houtman, R; et al. (Elsevier, 2018)
Macrophages polarize into distinct phenotypes in response to complex environmental cues. We found that the nuclear receptor PPARγ drove robust phenotypic changes in macrophages upon repeated stimulation with interleukin (IL)-4. The functions of PPARγ on macrophage polarization in this setting were independent of ligand binding. Ligand-insensitive PPARγ bound DNA and recruited the coactivator P300 and the architectural protein RAD21. This established a permissive chromatin environment that conferred transcriptional memory by facilitating the binding of the transcriptional regulator STAT6 and RNA polymerase II, leading to robust production of enhancer and mRNAs upon IL-4 re-stimulation. Ligand-insensitive PPARγ binding controlled the expression of an extracellular matrix remodeling-related gene network in macrophages. Expression of these genes increased during muscle regeneration in a mouse model of injury, and this increase coincided with the detection of IL-4 and PPARγ in the affected tissue. Thus, a predominantly ligand-insensitive PPARγ:RXR cistrome regulates progressive and/or reinforcing macrophage polarization.